Unconstitutional constitutional amendments : - Roznai, Yaniv (Oxford constitutional theory, 2017)
"Can constitutional amendments be unconstitutional? The problem of 'unconstitutional constitutional amendments' has become one of the most widely debated issues in comparative constitutional theory, constitutional design, and constitutional adjudication. This book describes and analyses the increasing tendency in global constitutionalism substantively to limit formal changes to constitutions. The challenges of constitutional unamendability to constitutional theory become even more complex when constitutional courts enforce such limitations through substantive judicial review of amendments, often resulting in the declaration that these constitutional amendments are 'unconstitutional'. Combining historical comparisons, constitutional theory, and a wide comparative study, [the author] sets out to explain what the nature of amendment power is, what its limitations are, and what the role of constitutional courts is and should be when enforcing limitations on constitutional amendments."--